Development and Validation of Canva-Based Interactive PowerPoint Media for Hot Beverage Instruction in Culinary Vocational Education - Dita Ayu Wulandari; Sri Handajani; Febriani Lukitasari; Hidayatun Muyasyaroh (IGI in Education Insight, 2026)
The accelerating digitalization of education has emerged as a defining global issue, fundamentally transforming pedagogical paradigms across primary, secondary, and tertiary learning environments. In the era of Industry 4.0 and Education 5.0, educational institutions worldwide are under increasing pressure to integrate innovative digital technologies that enhance instructional quality, foster learner autonomy, and develop future-ready competencies. This transformation is particularly significant in Technical and Vocational Education and Training (TVET), where educational effectiveness depends not only on conceptual understanding but also on the successful integration of practical, industry-relevant skill development. Across both developed and developing nations, vocational education systems are increasingly challenged to modernize instructional strategies in response to evolving workforce demands, technological advancements, and student preferences for flexible, interactive, and multimedia-rich learning environments. Within vocational secondary education, especially in culinary and hospitality training, instructional delivery remains heavily dependent on conventional methods such as teacher-centered lectures, static PowerPoint presentations, textbooks, and printed modules. While these approaches may provide foundational knowledge, they often fail to adequately engage contemporary learners, who increasingly favor visually stimulating, interactive, and self-paced educational experiences. This pedagogical mismatch may hinder learner motivation, reduce cognitive engagement, and constrain skill acquisition, particularly in procedural subjects requiring sequential understanding and practical application, such as hot beverage preparation. Consequently, the modernization of vocational instructional media has become an urgent educational priority globally. Extensive international literature has consistently emphasized the pedagogical value of interactive multimedia in improving educational outcomes. Studies indicate that multimedia-based instructional designs can significantly enhance student motivation, academic performance, retention, and learner satisfaction by integrating multimodal elements such as text, animation, audio, video, gamification, and nonlinear navigation. Theoretical frameworks such as Mayer’s Cognitive Theory of Multimedia Learning further support the integration of interactive digital resources, suggesting that appropriately designed multimedia can optimize cognitive processing by reducing extraneous load and enhancing meaningful learning